ANALYSIS OF WORKLOAD AND WORK-RESULT LEVELS ON WORK FATIGUE IN ELEMENTARY SCHOOL TEACHERS IN WEST KARAWANG DISTRICT - Sigit Mulyono; Henny Permatasari; Sudiono Sudiono (Universitas Pahlawan Tuanku Tambusai, 2023)
Work exhaustion is a weakening of energy to carry out an activity or a decrease in work power and a decrease in the body's resistance to work. Fatigue causes teacher performance to be disrupted. The purpose of this study was to identify the level of workload, stress, and work fatigue in elementary school teachers. The research method used is quantitative analytic descriptive with cross-sectional research design. The research sample was 190 teachers, taken using consecutive sampling technique. Bivariate analysis using the chi-square test showed a significant relationship between workload and stress levels with the occurrence of work fatigue in elementary school teachers. The findings of this study suggest the need to conduct promotive and preventive services and routine health screening in schools so that elementary school teachers can work optimally and avoid work fatigue problems.